GUARANTEEING THE ACCES OF THIRD PARTIES TO THE NETWORK INDUSTRIES SPECIFIC INFRASTRUCTURES – A VITAL COMPONENT OF EU'S POLICY IN THE FIELD OF COMPETITION ON THE ENERGY MARKET, IN THE CONTEXT OF THE NEED TO INSURE ENERGY INDEPENDENCE WHILE MANTAINING AFFORDABLE PRICES - Iulian BĂICULESCU; Dragoș-Adrian BANTAȘ (Challenges of the Knowledge Society)
As both the practical experience and the theoretical constructions of successive generations of practitioners and researchers of the phenomenon of the economy and the legal norms associated with its proper functioning have proven, the most important mechanism for increasing consumer satisfaction in a market, both from the perspective of the quality of the goods and services they benefit from, as well as from that of the prices demanded, is the competition. But in order to fulfill its otherwise noble functions, the competition must take place freely, since only then can it be considered genuine. Any deterioration of the free nature of competition results in a proportional decrease in consumer satisfaction (from the perspective of both previously identified dimensions) and, at the same time, an exponential deterioration of the functionality of the market in which competition occurs. From all these main considerations, but also in the light of the American experience, capitalized on the occasion of the recovery policies implemented as a result of the Great Crisis, exported through the conditionalities associated with the Marshall Plan, the European Communities and, subsequently, the Union have carried out a constant and active policy in the field of competition, whose legal basis is represented by numerous provisions of primary law, supplemented by provisions of secondary law and, of course, a rich jurisprudence on the matter. Ensuring free competition in the energy field is also part of this policy, an aspect that is consistent with the Union's policy in this aforementioned field. However, considering the impact of the war in Ukraine and the effects of the sanctions imposed on Russia on the review of the energy supply sources of the member states, aspects such as free competition in the energy field and the effects of the liberalization of this market on consumers become even more important, the more the price of energy resources increase or close to the origin of the inflationary phenomenon they are. Precisely for these reasons, our research will explore the issue of guaranteeing access to the infrastructures specific to the energy sector as a way of implementing the desired Union policy in the field of competition on the energy supply market.